REGULATORY ASPECTS OF AGRIBUSINESS ENTITIES DEVELOPMENT - I. Papakhchyan; A. Tolmachev (Вестник университета)
The authors presents the system representation of the process of interaction between the state and the subjects of agricultural production, supplemented by the block of regulation of the development of large, medium and small agricultural farms. The methodical approach of determination of economic eciency of measures of the state it allows to take into account and use in the right direction the factors of inuence of exogenous impacts, which are dicult controlled by business. It is proposed to improve the mechanism of state support, to orient the expenses of budget expenditures on the formation of the nal result. The criteria of the nal result is proposed to supplement the indicator of social eect - the number of jobs created and additional budget revenues